Locating India in the Contemporary International Legal Order (Springer India, 2018)
This book brings together disparate views which attempt to locate India in the contemporary international legal order. The essays endeavour to explore critically India's role and attitude towards international law in various fields and its influence and contribution in the development of the latter. The contributions are also of historical value, as they analyse the present as part of a historical trajectory. Drawing upon the current and historical practices from their respective fields, the authors attempt to highlight some critical aspects involving India and international law. These aspects broadly underline India's drift from its traditional role as an ally and proponent of the third world towards the pragmatism of self-interest, behaviour that is often compelled by internal political and economic conditions, as well as the dictates of external forces.